(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the role of anthropogenic, wind, food plants and temperature factors in the distribution of Lepidoptera insects.Of particular importance in the spread of the Glyphodes pyloalis in the Ferghana Valley were human activities and wind. During 1997-2001, the average annual spread rate of the Glyphodes pyloalis to the eastern regions of the Fergana Valley was 25.4 km, to the north - 14.6 km, to the southern borders - 7.8 km. Grapholitha molesta during the laying period can fly up to 200-300 meters across the garden. Also during the night it spreads for 2-5 km in the direction of the wind.